Features of dry eye manifestations in patients with different durations of diabetes mellitus (Ukrainian Journal of Ophthalmology, 2025)
Background: The risk of the development of proliferative diabetic retinopathy as well as abnormalities in the structure and/or function of the lacrimal functional unit significantly increases with an increase in diabetes mellitus duration, potentially leading to the development of dry eye.Purpose: To assess the state of the lacrimal functional unit in diabetic patients with dry eye and different durations of diabetes.Material and Methods: One hundred and twenty patients with both type 2 diabetes mellitus and dry eye disease were included in the study. Hemoglobin A1c levels and clinical manifestations of diabetic polyneuropathy and dry eye disease were comprehensively assessed.Results: We found that diabetes duration plays a dominant role in the nature of the course of dry eye disease in patients with type 2 diabetes mellitus. The main features of manifestations of dry eye disease in patients with diabetes mellitus are the predominance of the subjective symptoms in those with shorter diabetes duration and the absence of complaints of eye dryness as well as the presence of objective structural changes in the lacrimal functional unit in those with longer diabetes duration.Conclusion: Patients with long duration of diabetes mellitus have a latent course of dry eye disease and relatively severe structural abnormalities in the lacrimal functional unit.
Keywords: type 2 diabetes mellitus; diabetic polyneuropathy; dry eye disease